Peran Regulasi Emosi Siswa dalam Menghadapi Depresi: Studi SMK X Jurusan Teknik Komputer Jaringan - Syaputri, Ambar Aulia; Idulfilastri, Rita Markus (Lembaga Yasin AlSys, 2025)
Adolescent mental health problems, particularly among students in vocational high schools (SMK), are becoming increasingly prominent and constitute a critical concern in educational settings, including among students in the Computer and Network Engineering (Teknik Komputer dan Jaringan, TKJ) Department at SMK X who face academic pressure, limited emotional support, and the absence of counseling services, all of which contribute to the emergence of depressive symptoms. This study aims to understand the role of emotion regulation in dealing with depression among TKJ students at SMK X. A non-experimental quantitative method was employed, involving 150 students aged 15–18 years. Data were collected using the Emotion Regulation Questionnaire (ERQ) and the Beck Depression Inventory-II (BDI-II), and analyzed using Spearman correlation and simple linear regression. The findings show that emotion regulation has a significant effect on depression, accounting for 33.4% of the variance in depressive symptoms. The cognitive reappraisal strategy has a positive relationship with depression, indicating that the more frequently students change the way they think about emotional situations, the higher their depressive symptoms. Conversely, expressive suppression shows a negative relationship with depression, meaning that the greater their ability to suppress emotional expression, the lower the depressive symptoms they experience. These findings confirm that certain emotion regulation strategies are not yet fully adaptive for students and underscore the importance of paying attention to emotion regulation in understanding the dynamics of depression among vocational high school adolescents.